Multi Document Summarization Based On Cross-Document Relation Using Voting Technique - Jaya Kumar, Yogan; Salim, Naomie; Abuobieda, Albaraa; Tawfik , Ameer (2013)
News articles which are available through online search often provide readers with large collection of texts. Especially in the case of news story, different news sources reporting on the same event usually returns multiple articles in response to a reader’s search. In this work, we first identify cross-document relations from un-annotated texts using Genetic-CBR approach. Following that, we develop a new sentence scoring model based on voting technique over the identified cross-document relations. Our experiments show that incorporating the proposed methods in the summarization process yields substantial improvement over the mainstream methods. The performances of all methods were evaluated using ROUGE—a standard evaluation metric used in text summarization.